Electroantennographic response and odorant-binding protein expression alterations induced by host plant volatiles in Athetis dissimilis (Hampson) - Song, Yue Qin; Zhang, Tian Si; Yuan, Hao Zhan; Han, Sheng Jie; Li, Bo Liao (Frontiers in Physiology, 2025)
Athetis dissimilis is one of the main pests affecting crops, and is currently managed through chemical control methods. Plant volatiles can stimulate insects to feed and lay eggs. The investigation of plant volatiles and the development of effective attractants are essential for sustainable pest control. In this study, we examined plant volatiles using electroantennogram (EAG) analysis, and observed alterations in OBP expression in A. dissimilis. The EAG results indicated that the EAG responses for trans-2-hexenal, cis-3-hexen-1-ol, and trans-2-hexen-1-ol in male adults were the highest, measuring 1.35 ± 0.02 mV, 1.30 ± 0.10 mV and 1.27 ± 0.18 mV, respectively. This was followed by (E, E)-2,4-hexadienal (1.01 ± 0.06 mV), octanal (0.69 ± 0.04 mV), hexanal (0.67 ± 0.04 mV), benzothiazole (0.64 ± 0.01 mV), and benzyl acetate (0.61 ± 0.02 mV). The EAG responses of male adults towards the ligands above were generally higher than those of female adults. After fumigation, the expression levels of AdisOBPs in both female and male antennae exhibited varying degrees of increase compared with non-fumigated antennae. The expression levels of AdisOBP9 and AdisOBP11 in female antennae were significantly higher than those in the paraffin control after fumigation with β-caryophyllene. In addition, after fumigation by β-caryophyllene, the expression levels of AdisOBP9, AdisOBP11, AdisOBP24 and AdisOBP21 in male antennae increased significantly compared with those in the paraffin control. Similarly, after fumigation with benzyl acetate, the expression levels of AdisOBP9, AdisOBP11, AdisOBP24, AdisOBP21, AdisOBP7, AdisOBP4 and AdisOBP50 in male antennae were significantly elevated compared with those in the paraffin control. The number of upregulated genes was greater in male adults than in female adults, which aligns with the results of the EAG test. That is to say, male adults exhibited a stronger response to odor stimulation than female adults. Our findings provide valuable insights into the olfactory mechanisms of insects and contribute to the development of new environmentally friendly pest control methods.